Academic Superstitions of Pre-Service Teachers: Input Positive Mental Attitude Promotion Program - Ivy Mae Credo; Rhenshayne Adoptante; Razeline Grace Dela Paz - Olaje; Resha May Espinosa; Ruel Bonganciso (Research Synergy Foundation, 2023)
The study explores the academic superstitions of the pre-service teachers in Philippine Normal University Visayas and to find out whether these beliefs have positive impact to their mental attitude with regards to the promotion of their chosen programs. This is a mixed method research that specifically uses the explanatory sequential method design which employed the researcher-made questionnaire and an interview guide as tools to gather data. Stratified sampling was utilized to come up with the seventy-two (72) respondents. The statistical tools used in the study were the mean and standard deviation. Percentage, ranking, test, and one-way-ANOVA were used as well. For the qualitative data, this study used thematic analysis. Results provide a significant insight into the contemporary student mindset, showing that superstitions are not merely disregarded as irrational notions but are acknowledged to have a substantial role in both academic and personal growth. Also, students’ alignment or divergence concerning superstitions’ effect on academics is not notably influenced by their native language. In the same vein, results indicate that gender does not have a decisive role in shaping students’ views on superstitions in an academic context. Hence, external factors like personal experiences, family beliefs, and broader cultural influences may wield a greater influence in shaping students’ perceptions of superstitions with academic settings. The presented results offer a distinctive contribution to our comprehension of superstitions and their impact on mental outlook, psychological processes, and resultant behaviors. Simultaneously, these findings propose avenues for further exploration of superstitions.